Preparation and Characterization of Co(II), Ni(II) and Cu(II) New Schiff base complexes derived from acetoacetanilide - Muna Abass Hadi, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Solid metal complexes of Co(II), Ni(II),and Cu(II)have been preparation andcharacterization using anew Schiff base (ANPHA) derived from anew azo dye wasÎ²-[(p-(Nitrophenyl)azo] diketonilideand 4-aminoantipyrine characterized by several techniques, including elemental analysis (C.H.N), molar conductance, magnetic measurements, electronic spectral and IR spectral studies. The data show that these complexes have composition of [ML2] type. Theelectronic spectral, and magnetic susceptibilitydata of the complexes suggest octahedral geometry of all complexes, and the ligand (ANPHA) behaves mono basic tridentate manner, by coordination through the azomethine nitrogen atom and oxygen atoms.